KESEDERHANAAN KE ARAH PERPADUAN KAUM DI MALAYSIA - Ismail, Hamidi; Hassan, Kalthum; Zakaria, Mohd Nizar (Journal of Techno-Social, 2016)
There appear to be fewer discussions by previous authors on the government’s efforts to unite people through relationship of moderation in national policies. This article aims to discuss the issue of the linkages between the basic framework of the importance of moderation and racial unity. This article explains the 1Malaysia concept that was able to become an important channel to form national unity should each race practice moderation. Only moderation will unite, dilute and lessen feelings of extreme nature that tend to form racial disunity. In fact, 1Malaysia concept was also found to conform to the principles of Islam which emphasizes on moderation and these principles are consistent with human nature. Thus, this article is of the opinion that the value of moderation can establish racial unity in Malaysia if they are embraced and implemented in all aspects of life. This writing also found that in order to achieve Vision 2020, 1Malaysia concept can be considered as a navigator and catalyst for racial unity in accordance with the teachings of Islam and the needs of the todayâ€™s world which has been increasingly challenged by various forms of extremism.